(untitled) (Proceedings of the International Conference on Education, 2022)
The concept of English for Specific Purposes (ESP) was embraced in Nigeria in 1984 as an innovative methodology that would address students’ deficiencies in higher academic reading and writing. The learner-centered approach advocated by Hutchinson and Waters resulted in a new course being designed to teach the ESP sub-category known as English for Science and Technology (EST) to prepare learners to communicate effectively in their fields of specialization. For two decades, this approach impacted positively on language use but in recent times, challenges that adversely affect the quality of student learning and by implication the much desired development of science and technology in Nigeria have become apparent. While much research has been conducted in ESP, the question of how well ESP courses are being delivered in the classroom has largely been overlooked. Hence, these retrospective reviews the process of implementing an ESP/ EST course at FUT, Minna and the difficulties of maintaining teaching and learning quality. The efficacy of the course is examined via a survey of present learners’ views on teachers, course materials, and overall assessment of the course which revealed that the institutional status of the EST course, teachers’ skills and government policy are key factors for the success of this language approach. Some recommendations follow that will help inform the conduct and future direction of the ESP/EST in second language learning contexts such as found in Nigeria.